Efeito do habitat e da interação interespecífica na ocorrência de três espécies do gênero Leporinus (Characiformes; Anostomidae) em riachos neotropicais - Arnhold, Tatiane Regina (2016)
The occupancy can be defined as probability of a specie occupy a site over a given period. Occupancy models relate the probability of occurrence with habitat characteristics, considering the probability of detection and thus minimizing sampling bias. However, biotic interactions may also influence the occurrence of species. Species that are morphologically similar tend to compete more for using similar resources. In this context, the aim of this study was to identify environmental variables that influence the probability of occurrence of the species and the role of interspecific interaction in this probability. For this, we used three fish species of the genus Leporinus (L. friderici, L. octomaculatus, L. striatus). Collected data presence and absence of species by three divers in two rivers in the Midwest region of Brazil. Besides the detection history, we collect data on the following variables: water flow, canopy cover, substrate size and neighborhood occupation. We modeled the occupation of species using occupation model "single season single species" and the interaction between them with conditional occupancy models "single season two-species". For Leporinus friderici specie, the occupation was influenced by the water flow and of neighborhood occupation, to Leporinus striatus variables that influenced the occupation were water flow and size of the substrate, and L. octomaculatus was canopy cover and the neighborhood occupation. Leporinus octomaculatus apparently follows the two other congeners species, whereas L. friderici and L. striatus apparently occur independently. There is no evidence of competition.